Possible Nagashima-Type Palmoplantar Keratosis in Two Siblings - Kio Park; Kenji Kabashima; Yoshiki Miyachi (Karger Publishers, 2013)
Nagashima-type palmoplantar keratosis (PPK) is an autosomal recessive, transgressive and non-progressive form of PPK. It was once described as a mild form of mal de Meleda, but it is now proposed as a novel entity of PPK. Since its pathogenesis remains unclear, it is important to clarify the mode of inheritance. Here, we present a case of possible Nagashima-type PPK in 2 siblings. The siblings had non-affected parents, suggesting that the mode of inheritance was autosomal recessive. At present, reports on PPK in the English literature are limited, and thus the clinical features of Nagashima-type PPK may not be well appreciated in Western countries. More reports and concise clinical observations with genetic studies are required to establish this new entity of PPK.